Cubic Spline Model for Kinematic Analysis of the Badminton Smash Movement - Rahma Dhiyaa Sausan; Said Munzir; Vera Halfiani; Muhammad Ikhwan ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2025)
Smash is one of the most complex movements in badminton. Along with its development, quantitative analysis is needed to obtain the best smash movement. This research aims to analyze the smash movement kinematically through mathe matical means. The data in this study are primarily obtained through recording and digitizing data on the smash movement of one Aceh Province badminton athlete. The method used to analyze the data is the cubic spline method. This research produces smash movement kinematic data and analysis of translational and angular curves obtained using a cubic spline interpolation approach for three-dimensional coordinates. The kinematic aspects consisted of body segment position, body segment velocity and acceleration, also angular velocity and acceleration. The conclusion of this research is analysis of the best movement pattern to perform smash in badminton athletes can be conducted by analyzing the translational and angular curves. Those curves obtained by using the cubic spline interpolation approach for position coordinates in three dimensional space.